121k views
4 votes
1. Show that the function G(x)=x+3/2 is the inverse of F(x) = 2x – 3. Step 1: The function notation F(x) can be written as a variable in an equation. Is that variable x or y? Write F(x) = 2x – 3 as an equation with your chosen variable. (2 points) Step 2: Switch the variables in the equation from Step 1. Then solve for y. Show your work. (2 points) Step 3: Show that G(x)=x+3/2 is the inverse of F(x) = 2x – 3. Write your answer in inverse notation. (2 points)

2 Answers

1 vote

Answer:

gjgj

Explanation:

gogog

User SpaceDogCS
by
4.7k points
7 votes

Answer:

see below

Explanation:

F(x) = 2x – 3

Replace f(x) with y

y =2x-3

Exchange x and y

x = 2y-3

Solve for y

Add 3

x+3 = 2y-3+3

x+3 = 2y

Divide by 2

(x+3)/2 = 2y/2

(x+3)/2 =y

The inverse is (x+3)/2

G(x) = (x+3)/2

F ^-1 (x) = (x+3)/2

User Svenja
by
6.0k points